Analisis Pola Asuh Orang Tua Terhadap Perkembangan Karakter Anak Usia Dini - Mutiara Zahranti; Mohammad Rafli Kurnia; Mochamad Rizky Ramadhani; Rama Wijaya Abdul Rozak (Politeknik Kampar, 2024)
Parental parenting tends to determine children's attitudes and feelings in their daily lives. Indirectly, parents have a big influence on children's development. Many parents make mistakes in implementing parenting styles towards their children, so that the child's character becomes emotional, rebellious and stubborn. This research aims to analyze good and effective parenting patterns on the character development of early childhood. This research uses a qualitative approach with a focus on semi-structured interviews and participant observation to support and gather information. The research participants were 5 parents who had young children and used different parenting styles. In general, parents apply a democratic parenting style, because they consider this parenting style to be the best for developing a child's character. Through open communication, children will be honest with their parents and obey the rules well. Parents also believe that a democratic parenting style will make children have a high sense of self-confidence, independence and responsibility.